Efficient Network Reconfiguration Using Minimum Cost Maximum Flow-Based Branch Exchanges and Random Walks-Based Loss Estimations - Ababei, C; Kavasseri, R (IEEE transactions on power systems, 2011)
The efficiency of network reconfiguration depends on both the efficiency of the loss estimation technique and the efficiency of the reconfiguration approach itself. We propose two novel algorithmic techniques for speeding-up the computational runtime of both problems. First, we propose an efficient heuristic algorithm to solve the distribution network reconfiguration problem for loss reduction. We formulate the problem of finding incremental branch exchanges as a minimum cost maximum flow problem. This approach finds the best set of concurrent branch exchanges yielding larger loss reduction with fewer iterations, hence significantly reducing the computational runtime. Second, we propose an efficient random walks-based technique for the loss estimation in radial distribution systems. The novelty of this approach lies in its property of localizing the computation. Therefore, bus voltage magnitude updates can be calculated in much shorter computational runtimes in scenarios where the distribution system undergoes isolated topological changes, such as in the case of network reconfiguration. Experiments on distribution systems with sizes of up to 10476 buses demonstrate that the proposed techniques can achieve computational runtimes shorter with up to 7.78 times and with similar or better loss reduction compared to the Baran's reconfiguration technique .